"Sweetheart, I wish you Could Text without Help": Mediating Emotional Communication within the Context of Close Personal Relationships - Green, Sara E.; Brightman, Beth; Kassner, Katie (Disability Studies Quarterly, 2012)
This article explores the emotional challenges of mediated communication from the point of view of mediators who have close personal relationships with the people for whom they perform the mediating role. The article is based on the personal experiences of the three authors and on qualitative analysis of interviews with mothers and fathers of seven young adults who rely on mediated communication in their everyday lives. Our narrative highlights six key themes related to mediation within the context of close personal relationships: 1.The importance of parent/child communication; 2.The development of idiosyncratic communication systems – sometimes in defiance of professional constructions of what constitutes "real communication;" 3. The continued need for mediation after independent communication techniques have been mastered; 4. Parental concern about who will mediate in their absence; 5. Complications involved in parental mediation during the transition to adulthood; and 6.The problem of "blended voices" when both the mediator and communicator have an emotional stake in the communication. Keywords: Disability, Mediated Communication, Caregiving, Emotion, Close Relationships